TUANKU NAN RENCEH (1762-1832) - Irwan Setiawan (Diakronika, 2017)
Tuanku Nan Renceh was an Islamic cleric (ulama), leader and commanding figure who held in Indonesia History as a fighter against the Dutch colonialism in the battle known as the Padri War in Minangkabau. In contrast to this, the existence of this figure in history, was generally considered as a controversial figure who was responsible for the violence and bloodshed. Ironically, this figure appeared as a completely controversial figure on account of the written sources generally referred to him as an emotionally charged, fierce and frightening character. The source came from the enemy of Tuanku Nan Renceh at that time. When searching about his biography, it was very rarely obtained information about the history of life, family, struggle and the end of his life. The recent short article revealed the life history of Tuanku Nan Renceh and his valuable contribution for Minangkabau history in the days of Padri. Through this formulated paper, it is expected the life history of Tuanku Nan Renceh can be discovered. Most importantly, the respected readers can also assess his presence in more neutral position and do not discredit his character as a radical figure.